Tailored heating of forging billets using induction and conduction heating approaches. Issue 1 (16th December 2019) - Schulze, Martin; Baake, Egbert
Abstract : Purpose: This paper aims to deal with different induction and conduction heating approaches to realize a tailored heating of round billets for hot forming processes. In particular, this work examines the limits in which tailor-made temperature profiles can be achieved in the billet. In this way, a flow stress distribution based on the temperature field in the material can be set in a targeted manner, which is decisive for forming processes. Design/methodology/approach: For the heating of round billets by induction, the rotationally symmetric arrangement is used and a parameterized 2D finite element method model is created. The harmonic electromagnetic solution is coupled with the transient thermal solution. For heating by means of conduction, the same procedure is used only with the use of a 3D model. Findings: First results have shown that both methods can achieve very good results for billets with small diameters (d < 30 mm). For larger diameters, an adapted control of the heating process is necessary to ensure through heating of the material. Further investigations are carried out. Practical implications: Using tailored heating for forging billets, several forming steps can be achieved in one step. Among other things, higher energy efficiency and throughput rates can be achieved. Originality/value: The peculiarity of the tailored heating approach is that, in contrast to inhomogeneous heating, where only partial areas are heated, the entire component is heated to the target.